2012
DOI: 10.1007/s10875-011-9632-5
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of Multimeric-001—a Novel Universal Influenza Vaccine

Abstract: This vaccine model differs fundamentally from the current influenza virus vaccines, as it does not contain the variable regions of the virus hemagglutinin and hence does not induce hemagglutination inhibition antibodies that serve as surrogate markers for protection. In order to demonstrate the potential efficacy of the Multimeric-001, an alternative assay was employed, in which the lysis of MDCK cells infected with different virus strains was shown, with the involvement of the complement mechanism. The humora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
105
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(105 citation statements)
references
References 20 publications
0
105
0
Order By: Relevance
“…36 The study also included harboring diverse influenza B and T cell epitopes) with or without ISA 51. 11,12 In the study of Atsmon et al 2 immunizations were given and in the study of Pleguezuelos et al one immunization was given. Subjects in the phase I study of Pialoux et al all received 2 dosages of vCP125 antigens before they were randomized to receive 2 dosages of rgp160 antigens adjuvanted with alum or ISA 51.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…36 The study also included harboring diverse influenza B and T cell epitopes) with or without ISA 51. 11,12 In the study of Atsmon et al 2 immunizations were given and in the study of Pleguezuelos et al one immunization was given. Subjects in the phase I study of Pialoux et al all received 2 dosages of vCP125 antigens before they were randomized to receive 2 dosages of rgp160 antigens adjuvanted with alum or ISA 51.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…None of the participants in the adjuvant control groups developed AEs above moderate. 43 The prophylactic vaccine trials performed by Atsmon et al, Herrera et al and Pialoux et al reported the number of AEs after each immunization 11,41,42 . For the trial of Pleguezuelos et al, only the number of systemic AEs that occurred after a single injection could be extracted.…”
Section: Controlled Studies With Healthy Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vaccine company developer (BiondVax) is currently planning phase-III studies, 15 after completing phase-II clinical trials where Multimeric-001 Ò proved to be safe and immunogenic in humans and successfully stimulated both humoral and cellular immune responses against a wide variety of influenza A and B strains. 16 Readers should note that Multimeric-001 Ò has not yet been proven clinically to be a universal vaccine; the immunological data are supportive but its universality is yet to be proven.…”
Section: "Universal" Influenza Virus Vaccinesmentioning
confidence: 99%
“…18,19 DNA vaccines and peptide based vaccines have already been assayed in humans with promising results. 20,21 While many of these strategies proved to be very efficient and in some cases induced significant increases in cross-reactive immune responses, they did not completely solve the problems derived from the high antigenic variability of influenza virus.…”
Section: Development Of New Generation Vaccinesmentioning
confidence: 99%